Jane Eyre : un roman innovant pour les critiques victoriens - Odile Boucher-Rivalain (Revue LISA)
After the failure to publish her first novel The Professor Charlotte Brontë wrote her second work of fiction Jane Eyre in a conscious effort to satisfy the critics’ expectations, combining the more traditional elements of novel-writing with more innovating ones suggested by her own imagination. An examination of the reviews which appeared in the months following the publication of Jane Eyre reveals Charlotte Brontë’s strategy: her choice of an unconventional relationship between the poor, plain governess and her wealthy, passionate master, the exploration of her heroine’s interior life combined with the realistic descriptions of her characters’ physical and social environment. This combination ensured the success of the novel which was overwhelmingly praised for its innovative elements even if the more conservative critics disapproved of such novelties.